The bargaining position of outsourced labours in the ASEAN Economic Community (AEC) era - Sutinah Sutinah (Faculty of Social and Political Science, Universitas Airlangga, 2019)
This study was motivated by the increasing number of foreign manpower entering and working in Indonesia since the implementation of the ASEAN Economic Community (AEC) by the end of 2015. Therefore, this research intends to study the prosperity and the bargaining position of outsourced labours in the AEC era. To examine this, theories related to globalization and the free market, and issues related to employment were implemented. This research was conducted in an industrial area in Surabaya through questionnaires answered by 100 respondents who worked as outsourced labourers. Of this 100, 10 individuals participated in in-depth, structured interviews to supplement the data obtained through the questionnaires. There are a number of findings as a result of this research. Firstly, all respondents working as outsourced labourers are aware of the AEC and the impact of an increasingly difficult economic situation. Secondly, the low prosperity of outsourced labourers had in face occurred before the AEC. Outsourced labourers with a Specific Period Employment Agreement lacked job stability and had lower wages than permanent workers. Thirdly, the foreign manpower that has entered Indonesia has weakened the bargaining position of outsourced labourers as foreign workers are more highly educated and equipped with certified expertise and skills. The weak bargaining position of these workers is also due to the dropping union membership of outsourced labourers.